Adapt to the daily operations of campus security in the wake of COVID‐19. Issue 2 (17th May 2020) - Rahn, Josh
Abstract : The COVID‐19 pandemic has upended the normal routines of colleges and universities across the nation. Campus security departments are no exception. With fewer people on campus, their responsibilities have changed but not lessened. Campus security leaders must also consider the health threats posed to their own staff as they make assignments and monitor the unfolding pandemic.